Open cloud exchange (OCX): Architecture and functional components - Demchenko, Yuri; Van Der Ham, Jeroen; Ngo, Canh; Matselyukh, Taras; Filiposka, Sonja; de Laat, Cees; Escalona, Eduard (IEEE, 2013)
This paper presents the concept of Open Cloud eXchange (OCX) that has been proposed to bridge the gap between two major components of the cloud services provisioning infrastructure: Cloud Service Provider (CSP) infrastructure; and cloud services delivery infrastructure which in many cases requires dedicated local infrastructure and quality of services that cannot be delivered by the public Internet infrastructure. In both cases there is a need for interconnecting the CSP infrastructure and local access network infrastructure, in particular, to solve the "last mile" problem in delivering cloud services to customer locations and individual (end-)users. The OCX remains neutral to actual cloud services provisioning and limit its services to Layer 0 through Layer 2 to remain transparent to current cloud services model. The proposed document identifies the initial set of requirements to OCX, that can be run by NRENs, as a part of the GÉANT network, or jointly, and provides suggestions about OCX implementation. The proposed OCX concept will leverage the existing Internet eXchange (IX) and GLIF Open Lightpath Exchange (GOLE) solutions and practices, adding specific functionality that will simplify inter-CSP and customer infrastructure integration when supporting basic cloud services provisioning models, in particular Trusted Third Party (TTP) services to allow federated infrastructure and access control, commonly used by NRENs. The paper also describes trusted/secured topology exchange protocol and dynamic trust establishment protocol as a part of the OCX services.
Keywords: Intercloud Architecture Framework (ICAF); Open Cloud eXchange (OCX), Intercloud Federations Framework, Dynamic Trust Establishment